Synthesis and cytotoxicity of dithiocarbazate and thiosemicarbazide Schiff bases derived from chalcone and phenylbutanone analogues and their Cd(II) and Zn(II) complexes - Tan, Ming Yueh (2015)
Bidentate nitrogen-sulfur (NS) Schiff bases derived from the condensation of S-benzyl- (SBDTC) and S-methyldithiocarbazate (SMDTC) as well as N-phenyl- (PT) and Nmethylthiosemicarbazide (MT) with 4-substituted chalcone (H, Cl, OCH3 and NO2), phenylbutanone (H, OH, OCH3 and CH3-C(=O)) analogues and zingerone have been prepared. The Schiff bases were characterized using various physico-chemical and spectroscopic methods. The characterized Schiff bases were complexed with cadmium(II) and zinc(II) ions. A total of 50 metal complexes and 35 Schiff base ligands were synthesized and characterized. A total of 30 crystal structures were elucidated throughout this work. The metal complexes adopted either distorted tetrahedral or square planar geometries and coordinated with ligand in 1:2 mol ratios viaazomethine nitrogen and thiolo sulphur atoms in four-coordinated geometries. The cytotoxicities of synthesized and characterized Schiff bases and their complexes were evaluated against breast cancer estrogen receptor positive, MCF-7 and breast cancer estrogen receptor negative, MDA-MB-231 cell lines. It was found that Schiff bases which showed the most active cytotoxicity against MCF-7 and MDA-MB-231 were SM4ClTC and SB4ClTC, respectively. The IC50 values for SM4ClTC and SB4ClTC against MCF-7 and MDAMB-231 were 2.4 μM and 2.8 μM, respectively. Dithiocarbazate Schiff bases condensed with chalcone analogues were generally more active than the phenylbutanone derived thiosemicarbazones.